Uji Diagnostik Kriteria Baru Demam Reumatik - A. Samik Wahab A. Samik Wahab (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
More than 40 years ago T. Duckett Jones published a set of guidelines for the diagnosis of acute rheumatic fever that became known as the Jones criteria. The criteria became widely used throughout the world and provided a uniform diagnostic reference for national and international epidemiologic, prevention and treatment studies.Although the basic concepts proposed by Jones have been retained, modifications of the original criteria should be done to simplify the criteria in order to be used as a diagnostic tool at the primary health care, type D and C hospitals and for surveillance. These new simple diagnostic instruments should have good sensitivity, specificity, positive and negative predictive values using Jones criteria as gold standard.Eight criteria have been considered as a new simple 'diagnostic instrument, with various sensitivity, specificity, positive predictive and negative predictive values. The optimum result of this diagnostic test is in the eight criteria, i. e. the criteria of specific murmur.Key Words: rheumatic fever – cardiomegaly – heart failure – Jones criteria – specific murmur